The genus Paracholula (Hemiptera: Heteroptera: Lygaeoidea: Rhyparochromidae: Rhyparochrominae: Myodochini) - Peredo, Luis Cervantes; Santacruz, Jezabel Baez (Zootaxa, 2014)
The genus Paracholula Harrington has been represented by two species, P. picta (Fab) and P. thoracica (Distant), both recorded from Mexico. Individuals of one population from Guerrero were studied and compared with individuals of both species from different collections, including the types. Using scanning electron micrographs of different structures, and observation of the male genitalia of some individuals, together with a close examination of all the individuals from the population from Guerrero, we discovered, that there is great variation in all the structures and that some characters that were used to separate the two species are present within the population from Guerrero. Therefore we synonymize both species, stating that the valid name for this species is Paracholula picta (Fab). Descriptions and illustrations of all the immature stages from the Guerrero population are included. Notes about host plants, biology and distributional records are also included.